2020
DOI: 10.1108/tldr-03-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

Video-modelling as an effective solution for coaching carers of autistic adults

Abstract: Purpose Teaching skills to autistic individuals can increase independence and quality of life. However, staff supporting such individuals often lack the skills needed to teach skills. This study evaluated the use of digital videos (DVDs) to coach three care staff in teaching tooth-brushing skills to three autistic adults with co-occurring intellectual disabilities. Design/methodology/approach Personalized DVDs provided guidance on key elements of teaching new skills, including graded assistance, contingent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Few studies included data or a means for facilitating generalisation of taught skills across environments. Of all included studies within this review, only six were carried out in the natural context, such as the participant's home or in the community (e.g., grocery store) (Burckley et al, 2015; Cohen & McGill, 2020; Cruz‐Torres et al, 2020; Ford et al, 2020; Joshi, 2020; Lamash & Josman, 2021). Further, only an additional two studies demonstrated consideration of skill generalisation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Few studies included data or a means for facilitating generalisation of taught skills across environments. Of all included studies within this review, only six were carried out in the natural context, such as the participant's home or in the community (e.g., grocery store) (Burckley et al, 2015; Cohen & McGill, 2020; Cruz‐Torres et al, 2020; Ford et al, 2020; Joshi, 2020; Lamash & Josman, 2021). Further, only an additional two studies demonstrated consideration of skill generalisation.…”
Section: Resultsmentioning
confidence: 99%
“…Throughout most studies, short‐term maintenance data have been collected within a 3‐month window. Ten studies did not included any procedures to assess skill maintenance (Campbell et al, 2015; Caria et al, 2018; Cohen & McGill, 2020; Kellems et al, 2017; Lamash & Josman, 2021; Mechling et al, 2013; Pérez‐Fuster et al, 2019; Tomchek et al, 2017; Wertalik & Kubina, 2018; Wynkoop et al, 2018). Seven did not extend collection or analysis beyond 3 months (Brady et al, 2016; Burckley et al, 2015; Cruz‐Torres et al, 2020; Delisio & Isenhower, 2020; Ford et al, 2020; Gardner & Wolfe, 2019; Johnson et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations